KAJIAN GAYA BAHASA EKSPRESI CINTA PADA FILM ADA APA DENGAN CINTA 2: KAJIAN PSIKOLOGI STERNBERG - Luthfia Mutamami; Muh. Akbar Kurniawan Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the role of figurative language in constructing romantic narratives in film “Ada Apa Dengan Cinta 2” (2016) through the lens of Robert J. Sternberg’s Triangular Theory of Love. Using qualitative analysis, the research identifies metaphors, hyperboles, and personification in dialogues and narratives to explore how the three components of love, intimacy, passion, and commitment, are portrayed. Key findings reveal that metaphors dominate in illustrating emotional depth (intimacy), hyperboles emphasize enduring desire (passion), and process-oriented metaphors symbolize long-term dedication (commitment). The synergy of these stylistic devices reflects consummate love, highlighting the interplay of Sternberg’s components. This study bridges linguistic and psychological perspectives, demonstrating how figurative language enriches cinematic storytelling and deepens the audience’s emotional engagement.